Organization matters: the causes and consequences of organizational choices in the private and public sectors - Scur, D (2017)
This thesis explores organizational choices of establishments in the public and private sectors. Chapter 1 introduces the topic and details the motivating stylized facts from the main dataset used in this work: theWorld Management Survey (WMS). Chapter 2 focuses on family firms, the most prevalent type of firm in the world, and investigates the relationship between family control and quality of management in manufacturing firms as well the link to firm performance using two new datasets: the Ownership Survey and the WMS. The results suggest that family owned-and-controlled firms are worse managed, with coefficients being over twice larger under 2SLS than OLS. The negative link seems to stem from the family vs non-family control rather than simply family or non-family ownership. Chapter 3 develops a theoretical framework to understand one possible mechanism behind the low adoption of management practices at family firms. The model suggests that industry-specific parameters such as higher cost of laying off workers (ie. unionized environments), higher cost of firm reputation for family CEOs (ie. eponymous firms) and higher shares of low ability workers all contribute to lower adoption of management. Simple stylized facts are presented and testable implications requiring more rigorous tests are suggested. Chapter 4 details the development of an expanded evaluation tool for measuring quality of management in schools mirrored in the tool used in Chapter 2, the Development WMS (D-WMS), and presents the first stylized facts with new data from Mexico, India and Colombia. One of the stylized facts is that there is a large difference in management practices between private and public schools in India. Chapter 5 explores this further and results suggest that what drives the private school management premium is the better people management. Using additional detailed student- and teacher level panel data, I show that the combination of performance-driven teacher selection and pay practices may be behind the parallel private school student achievement premium as well.